Structured for success : what leaders need to know to build and sustain effective organizations - White, J. Chris; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Leadership is not just about reading data points and asserting corresponding action points; it is about designing an organizational structure and culture that directly generates desired performance results. Part of that involves understanding internal controls (such as motivation) versus external controls (such as policies and budgets) and making sure they cohere and never clash. From the perspective of sets and causal chains, the author presents a new way for leaders to view organizational structure holistically. A website accompanies the book with models and simulations that help map out these complex sets and predict/analyze results.
part Systems and Structure / J. Chris White -- chapter Leaders as Masters of Structure / J. Chris White -- chapter Feedback Loops as System Structure / J. Chris White -- part Consequence Maps / J. Chris White -- chapter Creating Consequence Maps / J. Chris White -- chapter Example Consequence Map for a City for a Major Change Initiative / J. Chris White -- chapter Example Consequence Map for a Non-Profit Organization for Grant Proposals / J. Chris White -- chapter Example Consequence Map for a Management Culture within a Defense Contractor Program / J. Chris White -- part System Dynamics Simulation / J. Chris White -- chapter Simulation Using System Dynamics / J. Chris White -- chapter Example Simulation for Reduction in Force (RIF) / J. Chris White -- chapter Example Simulation for Project Management / J. Chris White -- part Structured for Success / J. Chris White -- chapter Structured for Success / J. Chris White.
Keywords: Leadership; Organizational effectiveness